Ferroelectric and dielectric study in 0.78Na0.5Bi0.5TiO3-0.2SrTiO3-0.02K0.5Na0.5NbO3 lead free ceramic. (October 2021) - Singha, A.; Praharaj, S.; Rout, S.K.; Verma, R.; Rout, D.
Graphical abstract: Highlights: Constriction in P-E loops is correlated with defect dipoles and domain wall motion. Field-dependent P-E/J-E loops analyzed in the light of domain switching mechanism. Temperature induced phase transitions explained in terms of dynamics of PNRs. High ε r (>3200) maintained over a temperature range of ∼120–320 °C up to 1000 kHz. Dielectric loss remains within 10 % in the above mentioned temperature interval. Abstract: This study investigates the ferroelectric and dielectric behavior in lead-free 0.78Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.02K0.5 Na0.5 NbO3 ceramic synthesized by solid-state reaction. Application of electric fields (>30 kV/cm) induces a peculiar pinching effect on the P-E loops that may be attributed to the pinning of domain walls by defect dipoles. This is supported by the appearance of multiple peaks in J-E and ε( d P d E )-E loops. Domain wall motion/switching is discussed with regard to electric field dependence of hysteresis loop area . ε ( T, f ) and t a n δ T, f curves in the range 25–600 °C speculate the emergence of a modulated structure i.e. relaxor phase. Such behavior may be correlated to the evolution of highly polarizable dipolar entities (polar nano regions) of different symmetries. The gradual crossover of these polar nano regions results in temperature and frequency-insensitive dielectric permittivity (120–320 °C, and 1 to 10 6 Hz) with ε >3200 (±15 % fluctuation) at 150 °C.